2009
DOI: 10.1038/gt.2009.29
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells and T cells deliver oncolytic reovirus for tumour killing despite pre-existing anti-viral immunity

Abstract: Reovirus is a naturally occurring oncolytic virus currently in early clinical trials. However, the rapid induction of neutralizing antibodies represents a major obstacle to successful systemic delivery. This study addresses, for the first time, the ability of cellular carriers in the form of T cells and dendritic cells (DC) to protect reovirus from systemic neutralization. In addition, the ability of these cellular carriers to manipulate the subsequent balance of anti-viral versus anti-tumour immune response i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
139
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(148 citation statements)
references
References 39 publications
3
139
1
5
Order By: Relevance
“…Hence, reovirus oncotherapyactivated antitumor immune cells were transferred in reovirus-naive animals and then analyzed for their ability to restrict the growth of freshly implanted tumors. Further, recent reports have shown that reovirus loaded on immune cells can initiate the tumor regression on transfer of these cells (50). Thus, it can be argued that donor immune cells can acquire reovirus during virotherapy of primary tumors and carry it in naive host during transfer, and then restrict the development of secondary tumors after challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, reovirus oncotherapyactivated antitumor immune cells were transferred in reovirus-naive animals and then analyzed for their ability to restrict the growth of freshly implanted tumors. Further, recent reports have shown that reovirus loaded on immune cells can initiate the tumor regression on transfer of these cells (50). Thus, it can be argued that donor immune cells can acquire reovirus during virotherapy of primary tumors and carry it in naive host during transfer, and then restrict the development of secondary tumors after challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells (DCs) are professional antigen-presenting cells (APCs) that play critical roles in the activation of antigenspecific naïve T cells [7] and the regulation of the innate immune response [8] . The ability of DCs to deliver CRAds to metastatic melanoma cancer cells in vitro and in vivo has been demonstrated in a previous report [6] . CD40 is highly expressed on the surface of DCs.…”
Section: Original Articlementioning
confidence: 70%
“…Dendritic cells serve as a "Trojan horse" for oncolytic adenovirus delivery in the treatment of mouse prostate cancer defenses removes virus particles from the circulation, producing a major obstacle to achieving effective systemic delivery [6] . Dendritic cells (DCs) are professional antigen-presenting cells (APCs) that play critical roles in the activation of antigenspecific naïve T cells [7] and the regulation of the innate immune response [8] .…”
Section: Original Articlementioning
confidence: 99%
“…8 Several widely differing approaches aimed to protect circulating viral particles in the bloodstream to enhance tumor delivery are currently the focus of intense research. 9 Treatment with PEGylation, liposome encapsulation, cyclophosphamide or etoposide decreases the titer of neutralizing antibodies (Nabs) against adenoviruses and yield partial recovery of adenoviral infectivity in target cells upon a second injection. However, such modifications were ineffective in the case of third or later injections, owing to an increase in anti-adenovirus antibody titer, and, therefore, could not produce significant antitumor effects.…”
Section: Introductionmentioning
confidence: 99%
“…16 Preclinical studies have shown that different carrier-cell types, including T cells, monocytes, endothelial cells and tumor cells (autologous, allo-or xenogenic), can prevent systemic viral elimination. 9 The idea of using tumor cells as carriers to deliver a replicative virus was first demonstrated in a regional delivery of replication-selective HSV-1 for the intraperitoneal therapy of epithelial ovarian cancer xenografts. 17,18 Later studies, using a model of spontaneous metastases of human breast cancer, showed that intravenously (i.v.)…”
Section: Introductionmentioning
confidence: 99%